Antibiotic Sensitivity of Bacterial Pathogens in Urinary Tract Infections at Muhimbili National Hospital, Dar es Salaam, Tanzania (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Prevalence and sensitivity trends of urinary tract bacterial isolates were determined through a cross sectional retrospective study at Muhimbili National Hospital in Dar es Salaam. Four hundred specimens from 274 inpatients and 126 outpatients were studied and anti microbial sensitivity test was done by the disc diffusion technique. The results showed that among the isolated organisms the commonest were E. coli 44.75 %, Klebsiella spp. 33.00 %. Proteus spp. 10.50 %, Staphylococcus aureus 3.75 %, Streptococcus spp 3.75 %, mixed Coliforms 2.50 % and Pseudomonas spp 1.75 %. Of the total isolates 92.5 % were Gram negatives. Sensitivity tests against twelve antibiotics showed that resistance was common. Effectiveness of co-amoxiclav, cotrimoxazole, tetracycline, ampicillin and kanamycin was below 50.0 %. Their resistance rates were 53.9 %, 87.2 %, 85.7 %, 81.3 % and 53.9 % respectively. Gentamicin was tested in over 58 % of the common infective agents while ciprofloxacin was tested in over 71 % of all the isolates. It was observed that there was very high resistance to the commonly used antibiotics. The sensitivity rates for ciprofloxacin and gentamicin were found to be above 90 %. Therefore, these two antibiotics may be used for empirical therapy of urinary tract infections when culture and sensitivity tests are unavailable. Strict control on the use of antibiotics and appropriate measures against over the counter availability and self-medication is recommended.
Keywords: Antibiotic; UTI; Bacterial Sensitivity